The Role of Channa striata in Attenuating Inflammatory Markers (PCT, TNF-α, CRP) Following Intestinal Anastomosis in Hyperglycemic Rats: A Systematic Review and Dose-Response Meta-Analysis - Anangga Haryanto; Endang Sri Lestari; Sigit Adi Prasetyo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Hyperglycemia impairs wound healing and exacerbates inflammation, increasing the risk of complications following intestinal anastomosis. Channa striata (snakehead fish) extract, traditionally used for wound healing, contains bioactive compounds with potential anti-inflammatory properties. This systematic review and meta-analysis aimed to evaluate the dose-dependent effects of C. striata extract on procalcitonin (PCT), tumor necrosis factor-alpha (TNF-α), and C-reactive protein (CRP) levels in hyperglycemic rats undergoing end-to-end intestinal anastomosis. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, and Cochrane Library databases for studies published between 2013 and 2024. Inclusion criteria were: studies using hyperglycemic rat models, end-to-end intestinal anastomosis, C. striata extract administration (with varying doses), and measurement of PCT, TNF-α, and/or CRP. Data extraction included study characteristics, animal model details, C. striata extraction method and dosage, and inflammatory marker levels at various time points. Risk of bias was assessed using the SYRCLE's RoB tool. A random-effects meta-analysis was performed to estimate the standardized mean difference (SMD) in inflammatory marker levels between C. striata-treated and control groups. Dose-response relationships were explored using meta-regression. Results: Seven studies met the inclusion criteria. C. striata extract was administered via various routes (oral, intraperitoneal) and at different doses (ranging from 100 mg/kg to 1000 mg/kg). Meta-analysis revealed a significant reduction in PCT levels (SMD = -1.25, 95% CI: -1.80, -0.70; p < 0.001), TNF-α levels (SMD = -1.55, 95% CI: -2.15, -0.95; p < 0.001), and CRP levels (SMD = -1.38, 95% CI: -1.98, -0.78; p < 0.001) in C. striata-treated groups compared to controls. Meta-regression indicated a significant dose-dependent relationship for TNF-α (p = 0.02) and CRP (p = 0.04), with higher doses showing greater reductions. Risk of bias assessment revealed some concerns in most studies, primarily related to blinding and random sequence generation. Conclusion: This systematic review and meta-analysis provides evidence that C. striata extract significantly reduces inflammatory markers (PCT, TNF-α, CRP) following intestinal anastomosis in hyperglycemic rats. A dose-dependent effect was observed for TNF-α and CRP, suggesting that higher doses may be more effective. Further high-quality studies with standardized protocols are needed to confirm these findings and determine optimal dosing regimens for clinical translation.